2022
DOI: 10.3389/fnagi.2022.1021237
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment improves declined cognition induced by prenatal inflammatory exposure in aged CD-1 mice: Role of NGPF2 and PSD-95

Abstract: IntroductionResearch suggests that prenatal inflammatory exposure could accelerate age-related cognitive decline that may be resulted from neuroinflammation and synaptic dysfunction during aging. Environmental enrichment (EE) may mitigate the cognitive and synaptic deficits. Neurite growth-promoting factor 2 (NGPF2) and postsynaptic density protein 95 (PSD-95) play critical roles in neuroinflammation and synaptic function, respectively.MethodsWe examined whether this adversity and EE exposure can cause alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 72 publications
(155 reference statements)
2
4
0
Order By: Relevance
“…The present study demonstrated that long-term EE exposure improved MSD-induced depression and cognitive impairment in elderly mice. This result is consistent with the findings of our previous studies that EE alleviated the age-related cognitive impairment induced by prenatal inflammatory exposure ( Ni et al, 2022 ; Zhang Z. Z. et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study demonstrated that long-term EE exposure improved MSD-induced depression and cognitive impairment in elderly mice. This result is consistent with the findings of our previous studies that EE alleviated the age-related cognitive impairment induced by prenatal inflammatory exposure ( Ni et al, 2022 ; Zhang Z. Z. et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…The present study demonstrated that long-term EE exposure improved MSD-induced depression and cognitive impairment in elderly mice. This result is consistent with the findings of our previous studies that EE alleviated the age-related cognitive impairment induced by prenatal inflammatory exposure (Ni et al, 2022;. Collectively, these findings suggest that MSD results in behavioral difficulties in offspring that can persist into old age, which could be reversed by long-term EE.…”
Section: Ee Improves Msd-induced Depression and Cognitive Impairment ...supporting
confidence: 92%
See 2 more Smart Citations
“…It is reported that chronic restraint stress from GD 12 to 18 increases anxiety‐ and depression‐like behaviors in rat offspring (Lei et al., 2020). Our previous studies document that prenatal inflammation exposure significantly aggravates aging‐related learning and memory dysfunction (Ni et al., 2022; Zhuang et al., 2021). In the present study, the MSD‐induced mice displayed increased escape latency and distance during the learning phase and a decreased time and distance percent in the target quadrant during the memory phase, suggesting cognitive impairment induced by MSD.…”
Section: Discussionmentioning
confidence: 89%